Synthesis, characterization and applications of silver nanoparticles (Ag-NPs) in the field of electronics and optoelectronics device- A review - V.S. Chandak; P.V. Nagime (Hybrid Advances)
In nanotechnology, advancing dependable and environmentally sustainable methods for synthesizing silver nanoparticles (Ag-NPs) is essential. The methods for synthesis and their characterization methods are discussed in brief. Ag-NPs are among the most intriguing nanomaterials in a broad area of applications owing to physiochemical characteristics. This review offers a thorough examination of modern research on Ag-NPs in the fields of sensing, photovoltaics and electronics, electrochemical, optical devices, catalysts, and thermal applications, with a particular emphasis on their exceptional physical properties. This is primarily due to their compact size, proximity to biomolecules, higher surface area, high reactivity, and fast diffusion rate. This review also addresses the existing constraints and future potential of Ag-NPs for various sectors of applications.